The June 2010 Russian-Belarusian Gas Transit Dispute: a surprise that was to be expected - Yafimava, K (Oxford Institute for Energy Studies, 2010)
In June 2010 Belarus – the former Soviet country that does not feature too often in European media – attracted many headlines because of its transit dispute with Russia’s Gazprom. Presented with an ultimatum to repay its gas debt it five days or face supplies cuts, Belarus confronted Gazprom with a counter-demand to pay the debt for transit at an increased rate, threatening to reduce and potentially halt transit of gas and oil to Europe. This was not the first transit dispute between Belarus and Russia: the two countries went through several such incidents in the past, including in February 2004, January 2007 and January 2010. Only two past disputes – the 2004 gas dispute and the 2007 oil dispute – actually resulted in transit interruptions. All of these disputes were milestones marking the Russia’s quest to commercialise its gas and oil relationship with Belarus. The Russian government set this course in the early 2000s, once it had become clear that the project of political integration with Belarus had failed. Thus Russia decided to end various subsidies to Belarus – most significantly, the subsidy to Belarusian oil refineries provided by the sale of crude oil without export duty, and the subsidy included in cheap gas prices. The loss of $2bn in oil subsidies and an anticipated rise of gas bill created significant pressure on the Belarus’ finances, which were already under severe strain as a result of the financial and economic crisis of 2008. Aware of its decreasing negotiating power vis-à-vis Gazprom, because of the Nord Stream pipeline completion in 2012, Belarus attempted to use its (still important) gas and oil transit position to secure better commercial terms and thus improve its overall economic position. The worsening political relationship between the two countries may have made the achievement of this aim even more difficult.